Pengembangan Majalah Biologi (Biomagz) Pada Materi Virus Sebagai Alternatif Sumber Belajar Mandiri Siswa Kelas X di MAN 1 Mataram - Dani, Husnul Budiatman; Yahdi, Yahdi; Ningrat, Hadi Kusuma (Universitas Islam Negeri Mataram, 2017)
This study aims to examine the quality of application of biology magazine as an alternative self-learning resource for 10th year students in MAN 1 Mataram on Virus Material. This is a research and development study using ADDIE model which consist of Analysis, Design, Development and Implementation as well as Evaluation. To assest the quality of Biology Magazine (BioMagz), This was determined by assessment sheets (questionnaire) covering components includes the material/ content feasibility, linguistic and presentation. This Biology Magazine (BioMagz) was applied to 15 students of the 10th year in MAN 1 Mataram. The result showed that there was a significant different in learning outcomes of students whom Biology Magazine (Biomagz) was applied compared to students whom was conventional resoursce applied. This was shown by assessments of content completeness which was excellent with scores 100%, and Media worthiness reached scores 96% which was excellent, while evaluation result of field trials was good with scores 77,5%. This study suggested that Biology Magazine (BioMagz) can be used as an alternative self-learning resource to learn virus material in school.